1980
DOI: 10.1111/j.1348-0421.1980.tb02907.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Yersinia enterocolitica to Mammalian Epithelial Cell Lines

Abstract: Yersinia enterocolitica RIMD 2501003 grown at 25 C avidly adhered to various kinds of cultured epithelial cell lines (HeLa, FL, Y-1 adrenal, human intestine, human conjunctiva) but the bacteria grown at 37 C did not adhere. This phenomenon paralleled the temperature-dependent motility of the bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Measurement of the association of bacteria with animal cells in vitro has most commonly been made by microscopy of stained monolayers (Hartley et al, 1978;Hackney et al, 1980;Tavendale et al, 1983). Some procedures have divided the bacterial-animal cell interaction into two phases, the infection phase and the intracellular growth phase (Lee et al, 1977;Une, 1977 ;Une et al, 1977 ;Pedersen et al, 1979 ;Okamoto et al, 1980;Soemitro et al, 1981), a consideration that appears unnecessary with Y. enterocolitica because it does not multiply intracellularly (Devenish and Schiemann,198 1). Bacteria that do not associate with the animal cells during the interaction period are usually removed by repeated washing (Maki et al, 1978;Portnoy et al, 1981;Mintz et al, 1983) but density-gradient Received 10 Jul.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the association of bacteria with animal cells in vitro has most commonly been made by microscopy of stained monolayers (Hartley et al, 1978;Hackney et al, 1980;Tavendale et al, 1983). Some procedures have divided the bacterial-animal cell interaction into two phases, the infection phase and the intracellular growth phase (Lee et al, 1977;Une, 1977 ;Une et al, 1977 ;Pedersen et al, 1979 ;Okamoto et al, 1980;Soemitro et al, 1981), a consideration that appears unnecessary with Y. enterocolitica because it does not multiply intracellularly (Devenish and Schiemann,198 1). Bacteria that do not associate with the animal cells during the interaction period are usually removed by repeated washing (Maki et al, 1978;Portnoy et al, 1981;Mintz et al, 1983) but density-gradient Received 10 Jul.…”
Section: Introductionmentioning
confidence: 99%
“…enterocolitica at 35 -37°C has also been previously reported (Lee et al 1979;Okamoto et al 1980). Yersinia enterocolitica demonstrates many other temperature-dependent characteristics, including the synthesis of certain outer membrane proteins (Portnoy et al 1981;Portnoy et al 1984).…”
Section: Discussionmentioning
confidence: 52%
“…Recent studies using tissue culture monolayers have shown that association with Vero cells (ATCC CCL-81) was greater than with HeLa or Henle cells (unpublished data). Okamoto et al (1980) reported that Y . enterocolitica adhered equally well to HeLa, FL, Y-1 adrenal, Henle, and conjunctival cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some Y . enterocolitica adhere to epithelial cells when grown at 25°C but not at 37°C (Okamoto et al, 1980;Old and Robertson, 1981) and some adhere equally well after cultivation at 25°C or at 37°C (Lee et al, 1981 ;Old and Robertson, 1981). Because the VWderivatives showed adhesive ability with epithelial cells (Portnoy et al, 1981;Schiemann, 1981;Heesemann et al, 1983), the plasmid had not been considered to be involved in the adherence of pathogenic Y. enterocolitica.…”
Section: Discussionmentioning
confidence: 99%